213k views
1 vote
-4x-3y=5 3x-2y=-8 Solve by substitution

User DrDom
by
4.8k points

2 Answers

4 votes

Answer:

y=1

x=-2

Explanation:

Lets use substitution for the first equation:

-4x=5+3y

Divide by -4 on both sides : x=-5/4-3/4y

Now we substitute x into the second equation:

3(-5/4-3/4y)-2y=-8

Simplify : -15/4-9/4y-2y=-8

Combine Like Terms : -15/4-17/4y=-8

Isolate the Variable : -17/4y=-17/4

y=1

Now we get that x is -5/4-3/4, which is -8/4=-2

x=-2

User RSingh
by
5.3k points
6 votes

Answer:

look at the picture ..........

-4x-3y=5 3x-2y=-8 Solve by substitution-example-1
User Phisn
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.